Caracterização magnetométrica do sill de Limeira – SP - Seixas, Adriano da Rosa [UNESP]; Nardy, Antonio José Ranalli [UNESP]; Moreira, César Augusto [UNESP]; Pereira, Alice Marques [UNESP] (My University, 2015)
The purpose of this study is to characterize the geological subsurface structure of the diabase sill of the Paraná Magmatic Province intruded in the Itararé Group, located near the city of Limeira, in the east-central region of São Paulo state. The magnetometric method served as an important tool defining the igneous body in view of the great contrast between the physical properties of the diabase sill and the host sandstones. Previous cartographic data signaled in region a possible lateral continuity in subsurface, of the various sills that occur in the region. However, the magnetic data obtained herein indicate that the area of occurrence of this body is very restricted and independent of the others observed in the region. The analysis of the radial average power spectrum obtained allowed determine the interval of number of waves adequate for the separation of shallow and deep sources, and thus conclude that the sill of the Limeira region is located more than 100 m deep.
Magnetometric characterization of the sill of Limeira - SP